Myotendinous junction: a microenvironment favorable for short-term adaptations to resistance training following gastrocnemius muscle atrophy - Rocha-Braga, Lara Caetano; Pimentel Neto, Jurandyr; Gomes, Isabella; Ciena, Adriano Polican (Frontiers in Physiology, 2025)
The myotendinous junction (MTJ) is an interface region between the skeletal muscle fibers and the tendon, specialized in force transmission, and has a wide capacity to adapt to different stimuli. Disuse muscle atrophy is a deleterious effect of joint immobilization, which is used as a conservative treatment for bone, muscle, and joint injuries and promotes a significant functional decline. Physical exercise is an effective therapeutic modality in combating muscle atrophy, especially resistance training that promotes hypertrophic responses. We aimed to investigate the plasticity of the MTJ in rats subjected to joint immobilization, followed by resistance training in a short period (7 and 14 days). Forty-eight male Wistar rats (90 days old) were used and divided into groups (n = 8): Control (C), Immobilized (I), Trained (T), and Immobilized Trained (IT). The MTJ samples of gastrocnemius muscle were collected and processed for morphoquantitative analyses using transmission electron microscopy (MTJ and sarcomeres morphometry) and immunofluorescence techniques for collagen XXII, satellite cells and telocytes. We observed that the I group exhibited a reduction in muscle mass, which was associated with a decrease in the length of sarcoplasmic invaginations and evaginations, as well as reductions in belly and proximal sarcomere length. Conversely, the IT groups demonstrated a progressive increase in muscle mass, with significant improvements from 7 days (p < 0.01) to 14 days (p < 0.0001). The most pronounced adaptations in sarcoplasmic projections were observed in the IT14 group, which exhibited: a significant increase in the length of sarcoplasmic invaginations (p < 0.05); a marked increase in sarcoplasmic evaginations (p < 0.001); a substantial enlargement of the belly sarcomere (p < 0.0001) and proximal sarcomere (p < 0.0001); and a notable expansion of the collagen XXII perimeter (p < 0.001). We concluded that the joint immobilization resulted in muscle atrophy due to disuse, which led to a decrease in sarcoplasmic projections in the MTJ, a reduction in the perimeter of collagen XXII, and, consequently, fragility of the region. Short-term training demonstrated positive effects on functional improvement, partial recovery of muscle mass, and induction of hypertrophic responses, indicating positive repercussions for the structural recovery of the myotendinous region.